Preventive Effect of Wheat Germ on Hypercholesteremic and Atherosclerosis in Rats Fed Cholesterol-Containing Diet - Rezq, Amr A.; Mahmoud, Mohamed Y. (Pakistan Journal of Nutrition, 2011)
Wheat germ is one of the most potential and excellent sources of vitamins, minerals, fiber and proteins. The aim of the present study was to investigate the preventive effect of wheat germ on hypercholesteremic and atherosclerosis in rats fed cholesterol-containing diet. Five groups of rats were used; group (1) fed cholesterol free-diet (negative group); group (2) fed cholesterol-diet (positive group); groups (3), (4) and (5) were fed cholesterol-diets with adding 5, 10 and 15% wheat germ, respectively. Results revealed that positive control rats had significantly increased in serum levels of Total Lipids (TL), Triglycerides (TG), Total Cholesterol (TC), LDL-C, VLDL-C, GOT, GPT and ALP and significant decrease in serum level HDL-C which represented by increased atherogenic index as compared to the negative control groups. Histopathological examination showed that positive control rats had vaculations of tunica media, narrowing in the lumen, focal necrosis of tunica intima and tunica media associated with leucocytic cells infiltration of aorta. In addition to vaculations of cardiac myocytes associated with intramuscular edema as well as cytoplasmic vacuolization and fatty changes of hepatocytes. Feeding different levels of wheat germ caused significantly decreased in serum levels of TL, TG, TC, LDL-C, VLDL-C, GOT, GPT and ALP and significantly increased in serum level of HDL-C which represented with significantly decreased in atherogenic index as compared to the positive control group. Histopathological examination revealed that aorta, heart and liver sections of rats feeding 10 and 15% wheat germ had normal histological structure, except, some sections of group treated with 10 % wheat germ had small vacuoles in the cytoplasm of hepatocytes.